GW24-e3581 Patients with atrial fibrillation and other primary diagnosis in the emergency department: Baseline characteristics and outcomes. (1st October 2013) - Han, Zhang; Jun, Zhu; Yanmin, Yang
Abstract : Objectives: Atrial fibrillation (AF) is common in the emergency department (ED), however, patients with AF sometimes visit ED because of other primary reason. There are no data on the characteristics and outcomes of ED patients with atrial fibrillation who have other primary ED diagnoses. Methods: In this prospective observational multi centre registry study, all AF cases were confirmed by the electrocardiograms (ECGs) inthe ED from November 2008 to October 2011 in China. Repeat ED visits were excluded. By pulling all patient charts, we separated patients with a primary diagnosis of atrial fibrillation from those with other primary ED diagnoses, using the EPs' first diagnosis written on the ED chart. Patients demographics, medical history, type of AF, treatment, and outcome of emergency room visit were collected at baseline by the treating physicians using a standardised questionnaire. The main outcome measure was all-cause mortality at 1 year post-ED visit. As a secondary analysis, logistic regression was used to compare 1 year mortality of these patients to those with primary ED diagnoses of atrial fibrillation seen during the same time period. Results: During the study period, 2016 Chinese patients visited the ED, AF was the primary reason only in 825 patients (40.9%), while AF was the secondary diagnosis in the remaining patients. Patients with secondary AF diagnosis were older (69.8 ± 13.1 vs 66.6 ± 13.3) and thinner (BMI, 23.2 ± 3.6 vs 24.0 ± 3.5), while systolic blood pressure (SBP) washigher (133.8 ± 24.7 vs 129.0 ± 21.3) and heart rate was lower (97.4 ± 27.1 vs 107.9 ± 31.3). Permanent AF was more frequent (61.2% vs 26.3%) in patients with secondary AF diagnosis and they were less likely to be paroxysmal AF (21.1% vs44.5%). Meanwhile, the prevalence of risk factors and comorbidities, such asheart failure (49.1% vs 20.5%), coronary artery disease (46.6% vs 35.0%), stroke/TIA(11.7% vs 17.6%), valvular heart disease (19.6% vs 12.5%), and diabetes mellitus (17.2% vs 13.0%) was higher. Similarly, there was an increase in CHADS2 [cardiac failure, hypertension, age, diabetes, stroke (doubled)] score (2.1 ± 1.4 vs 1.4 ± 1.3), but there was no difference in antithrombotic therapy between two groups. The most common primary ED diagnoses were congestive heart failure (30.3%), respiratory diseases (7.7%), stroke/TIA (7.6%), dyspnea (7.1%), fever (7.0%), palpitation (6.0%), coronary arterydisease (6.0%), dizzy (5.7%), and chest pain not yet diagnosed (5.0%). 1-year mortality were 7.8% and 18.3%, respectively. In the adjusted analysis, an alternative primary ED diagnosis was associated with an increased risk of death (hazard ratio [OR] = 1.84; 95% CI, 1.38-2.46, p < 0.001). Conclusions: Patients seen in the ED with atrial fibrillation and different primary ED diagnoses are older and have more comorbities higher than patients with primary ED diagnoses of atrial fibrillation.1-year mortality was also higher in paitents with secondary AF diagnosis. Future studies of atrial fibrillation in the ED should distinguish between these two populations and the potential contribution of atrial fibrillation to mortality in the setting of other primary ED diagnoses.